2021
DOI: 10.9734/jammr/2021/v33i830881
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Accept COVID-19 Vaccine and Its Determinants among Nigeria Citizens: A Web-based Cross-sectional Study

Abstract: Background: The peculiarity in Nigerians’ demographic, socio-economic and cultural pattern necessitated the need to explore potential COVID-19 vaccine acceptance. This study investigated the determinants of willingness to receive COVID-19 vaccine in Nigeria. Methods: An online cross-sectional study among the general population in Nigeria. Data were collected using an electronic questionnaire.  A total of 368 individuals participated in the research. The outcome variable was willingness to accept COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 17 publications
3
30
0
Order By: Relevance
“…Consistent with other studies in Nigeria (Eniade et al, 2021), Ethiopia (Mant et al, 2021), andJordan (El-Elimat et al, 2021), fear of the safety of the vaccine, fear of adverse effects, the e cacy of vaccine, lack of trust in the government and knowledge about the vaccines were the major reasons for unwillingness to take the COVID-19 vaccine. A previous study among women in Northern Nigeria documented vaccine hesitancy as 13%.…”
Section: Covid-19 Vaccine Willingness Uptake and Unmet Needsupporting
confidence: 83%
See 2 more Smart Citations
“…Consistent with other studies in Nigeria (Eniade et al, 2021), Ethiopia (Mant et al, 2021), andJordan (El-Elimat et al, 2021), fear of the safety of the vaccine, fear of adverse effects, the e cacy of vaccine, lack of trust in the government and knowledge about the vaccines were the major reasons for unwillingness to take the COVID-19 vaccine. A previous study among women in Northern Nigeria documented vaccine hesitancy as 13%.…”
Section: Covid-19 Vaccine Willingness Uptake and Unmet Needsupporting
confidence: 83%
“…Vaccine hesitancy, a major impediment to vaccine uptake has been documented globally, but especially in Africa. A major concern towards the COVID-19 vaccine was the accelerated pace of the development of the vaccine, mistrust of the government's response, and safety (Eniade et al, 2021;Lazarus et al, 2020;Piot et al, 2019;Schaffer Deroo et al, 2020;Wang et al, 2020). It was reported by WHO that several African countries have paused COVID-19 vaccine rollouts because of safety concerns, due to fears of side effects reported in developed countries (WHO Africa, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, effective communication to create confidence and reduce public ambiguity is critical for promoting vaccination acceptability, willingness, and uptake, avoiding vaccine hesitancy, and dealing with any infodemic on the topic, such as in the case of COVID-19 vaccines. [27][28][29][30][31][32] has turned out to be unsuitable in addressing the issue. More so, it appears the body language of many Nigerians show likelihood and tendency of rejecting the vaccine even if it is made compulsory by the government.…”
Section: Introductionmentioning
confidence: 99%
“…Documented data showed that there were 150,308 documented recoveries from COVID-19 15,16 with some "No vaccine" advocates believing that vaccines are unwholesome tools for government control over the masses while others had hesitancy due to lack of trust in the government system and perceived risk of side effects of the vaccines.…”
Section: Recoveriesmentioning
confidence: 99%